Antibodies to Epstein-Barr virus and MRI disease activity in multiple sclerosis. (December 2014) - Kvistad, Silje; Myhr, Kjell-Morten; Holmøy, Trygve; Bakke, Søren; Beiske, Antonie G; Bjerve, Kristian S; Hovdal, Harald; Løken-Amsrud, Kristin I; Lilleås, Finn; Midgard, Rune; Njølstad, Gro; Pedersen, Tom; et al.
Background: Previous reports indicate an association between Epstein-Barr virus (EBV) antibody levels and multiple sclerosis (MS) disease activity, but the results have been conflicting. Objectives: The objective of this paper is to study if EBV antibody levels reflect MRI disease activity in MS and examine the potential for EBV antibody levels as biomarkers for treatment response. Methods: A total of 87 MS patients were followed for two years prior to and during interferon beta (IFNB) treatment, with MRI examinations and serum measurement of IgM and IgG antibodies to viral capsid antigen (VCA), EBV nuclear antigen 1 (EBNA-1) and early antigen (EA). Associations between EBV antibody levels and MRI activity were assessed by a logistic regression model. Results: Higher anti-EBNA-1 IgG levels were associated with increased MRI activity, OR = 2.95 (95% CI 1.07–8.10; p = 0.036) for combined unique activity (CUA; the sum of T1Gd+ lesions and new or enlarging T2 lesions). Although most patients were anti-VCA IgM negative, there was an inverse association, OR = 0.32 (95% CI 0.12–0.84; p = 0.021) with CUA during IFNB treatment. Conclusions: This study supports an association between anti-EBNA-1 IgG levels and MS disease activity. We also found an inverse association with anti-VCA IgM levels during IFNB treatment not previously described, indicating anti-VCA IgM as a possible biomarker for IFNB treatment response.